KAJIAN EKONOMI DALAM PENGENDALIAN KERUSAKAN LINGKUNGAN HIDUP - Drakel, Anhar (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
Environmental problems arise due to the interaction between economic activities and the existence of natural resources. The greater the amount and intensity of exploitation of natural resources, the impact on environmental degradation also tends to increase. The impacts or side effects (externalities) cover space and time. In addition, environmental impacts not only have local, regional, and global impacts, but also have short-term, medium-term, and long-term impacts on the environment. The problems in this study are as follows: (1) Economic and environmental perspectives on the use of natural resources (2) Environmental problems (3) Impacts of environmental damage on the economy and society (4) Implications of environmental quality control policies. The objectives of this study are as follows: (1) To find out how the economic and environmental perspectives are in the utilization of natural resources. (2) To examine the impact of environmental damage on the economy and society (3) To know and examine the policies needed in controlling environmental quality. Attention to environmental problems is still lacking. Policy formulation and implementation still need to be developed and refined further. Therefore, support from various elements in society is needed so that environmentally conscious development efforts can be realized. The role and political will of the government are the main keys to its success, in addition to the support and participation of other institutions such as economic actors, especially producers in the industrial and agricultural sectors, non-governmental organizations, mass media, which together with the support and participation of the community.